Pengaruh Penambahan Rempah Ketumbar (Coriandrum Sativum L.) Terhadap Cita Rasa Pada Rendang Daging Sapi Dengan Uji Hedonik - Indah Dwi Putri; Iswendi Iswendi; Iryani Iryani; Fitri Amelia (Jurnal Periodic Jurusan Kimia UNP, 2022)
Coriander (Coriandrum sativum L.) is a spice known to have active ingredients, one of which is anti-cholesterol. Some regions use coriander as an ingredient in making beef rendang. The purpose of this study was to determine the level of preference for color, meat texture, seasoning texture, taste and aroma of beef rendang made using six variations of the addition of coriander rhizome, namely with levels: 0, 1, 2, 3, 4 and 5 grams/500 grams. beef. The organoleptic test method uses the hedonic test, namely the level of preference test with 40 panelists of UNP chemistry students 2020. The hedonic test results show that, the addition of coriander seasoning to beef rendang in general there is no significant change (p> 0.05) to the original rendang.